Correction: Determination of aflatoxin M1 using an aptamer-based biosensor immobilized on the surface of dendritic fibrous nano-silica functionalized by amine groups. Issue 12 (15th March 2022) - Kholafazad kordasht, Houman; Moosavy, Mir-Hassan; Hasanzadeh, Mohammad; Soleymani, Jafar; Mokhtarzadeh, Ahad
Abstract : Correction for 'Determination of aflatoxin M1 using an aptamer-based biosensor immobilized on the surface of dendritic fibrous nano-silica functionalized by amine groups' by Houman Kholafazad kordasht et al., Anal. Methods, 2019, 11, 3910–3919, DOI: ; 10.1039/C9AY01185D .